2019
DOI: 10.1002/nbm.4111
|View full text |Cite
|
Sign up to set email alerts
|

Decreased water T2 in fatty infiltrated skeletal muscles of patients with neuromuscular diseases

Abstract: Quantitative imaging techniques are emerging in the field of magnetic resonance imaging of neuromuscular diseases (NMD). T 2 of water (T 2w ) is considered an important imaging marker to assess acute and chronic alterations of the muscle fibers, being generally interpreted as an indicator for "disease activity" in the muscle tissue.To validate the accuracy and robustness of quantitative imaging methods, 1 H magnetic resonance spectroscopy (MRS) can be used as a gold standard.The purpose of the present work was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 38 publications
10
44
1
Order By: Relevance
“…45 After correction for the increase of T2 caused by fatty infiltration, 46 we found a decrease in T2 that almost exactly follows the simulation of T2 against an increasing fat fraction, similar to a previous study. 26 Therefore, we conclude that a decrease of T2 as we perceived is solely related to partial volume effects caused by the amount of fat infiltration and that the T2 signal increase in itself does not indicate any pathological process. However, if the T2 relaxation of water in fat had a higher value of 30 ms instead of the assumed 20 ms, part of the decreased T2 could potentially be attributed to pathological processes.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…45 After correction for the increase of T2 caused by fatty infiltration, 46 we found a decrease in T2 that almost exactly follows the simulation of T2 against an increasing fat fraction, similar to a previous study. 26 Therefore, we conclude that a decrease of T2 as we perceived is solely related to partial volume effects caused by the amount of fat infiltration and that the T2 signal increase in itself does not indicate any pathological process. However, if the T2 relaxation of water in fat had a higher value of 30 ms instead of the assumed 20 ms, part of the decreased T2 could potentially be attributed to pathological processes.…”
Section: Discussionsupporting
confidence: 47%
“…This may be explained by atrophy of muscle fibers. The alternative explanation, in which the decrease of MD reflects changes in viscosity of the extracellular space due to fibrosis 26 is less likely, since it would be accompanied by an invariable FA, as the cellular dimension would not change. Therefore, we hypothesize that our DTI findings indicate ongoing muscular atrophy, fitting the histopathological characteristics of muscle tissue rather than fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most papers, using fat corrected T2 measurements, show increased T2 in myositis. 10,30 Schlaeger et al 31 found that T2 can decrease in neuromuscular disease patients; however, their study sample was heterogeneous including a range of muscular diseases along with myositis.…”
Section: Discussionmentioning
confidence: 94%